Stress-related reduction of hippocampal subfield volumes in major depressive disorder: A 7-Tesla study - Alper, Judy; Feng, Rui; Verma, Gaurav; Rutter, Sarah; Huang, Kuang-han; Xie, Long; Yushkevich, Paul; Jacob, Yael; Brown, Stephanie; Kautz, Marin; Schneider, Molly; Lin, Hung-Mo; et al. (Frontiers in Psychiatry, 2023)
Background Major depressive disorder (MDD) is a prevalent health problem with complex pathophysiology that is not clearly understood. Prior work has implicated the hippocampus in MDD, but how hippocampal subfields influence or are affected by MDD requires further characterization with high-resolution data. This will help ascertain the accuracy and reproducibility of previous subfield findings in depression as well as correlate subfield volumes with MDD symptom scores. The objective of this study was to assess volumetric differences in hippocampal subfields between MDD patients globally and healthy controls (HC) as well as between a subset of treatment-resistant depression (TRD) patients and HC using automatic segmentation of hippocampal subfields (ASHS) software and ultra-high field MRI. Methods Thirty-five MDD patients and 28 HC underwent imaging using 7-Tesla MRI. ASHS software was applied to the imaging data to perform automated hippocampal segmentation and provide volumetrics for analysis. An exploratory analysis was also performed on associations between symptom scores for diagnostic testing and hippocampal subfield volumes. Results Compared to HC, MDD and TRD patients showed reduced right-hemisphere CA2/3 subfield volume (p = 0.01, η2 = 0.31 and p = 0.3, η2 = 0.44, respectively). Additionally, negative associations were found between subfield volumes and life-stressor checklist scores, including left CA1 (p = 0.041, f2 = 0.419), left CA4/DG (p = 0.010, f2 = 0.584), right subiculum total (p = 0.038, f2 = 0.354), left hippocampus total (p = 0.015, f2 = 0.134), and right hippocampus total (p = 0.034, f2 = 0.110). Caution should be exercised in interpreting these results due to the small sample size and low power. Conclusion Determining biomarkers for MDD and TRD pathophysiology through segmentation on high-resolution MRI data and understanding the effects of stress on these regions can enable better assessment of biological response to treatment selection and may elucidate the underlying mechanisms of depression.